The complete mitochondrial genome of Traulia minuta Huang & Xia, 1985 (Orthoptera: Catantopinae) - Zhongying Qiu; Yuting Wang; Hao Yuan; Xuan Zhao; Ningyu Ru; Li Liu; Yuanyuan Cui; Yantong Liu (Mitochondrial DNA. Part B. Resources, 2021)
In the present study, we obtained and annotated the complete mitochondrial genome (mitogenome) of Traulia minuta. The length of the whole mitogenome was 15,636 bp and the AT content of the complete mitogenome was 74.5%. All protein-coding genes (PCGs) started with typical ATN codon and ended with complete TAA/TAG codons except Nad5, which ended with incomplete T codon. The phylogenetic tree indicated that T. minuta was clustered together with T. szetschuanensis.